POTENTIAL AND PROBLEM FOR DEVELOPMENT COASTAL ZONE IN KENDAL, CENTRAL JAVA - Abdul Rahman; Eppy Yuliani (International Conference on Coastal and Delta Areas, 2015)
Kendal coastal area has a beach along the 43.5 kilometers. In the coastal area there are also many excellent potential but has not been used optimally. And also have not been indentified community needs for development in the coastal area of Kendal. So it needs to be studied further. The final result of this study that there is a potential for coastal fisheries sector in Kendal such as the amount of land on the embankment in District Brangsong and District Cepiring. In addition, there are also 4 (four) Fish Auction Place (TPI), that is TPI Tawang, TPI Bandengan, TPI Sendang Sikucing and TPI Tanggul Malang. To the potential of the tourism sector that has been managed well is a tourist attraction Beach Sendang Sikucing and Curugsewu. Problems found in coastal areas Kendal such as silting up the harbor pool in District Rowosari, breakwater already there yet function optimally in District Kendal. Besides not optimal utilization of fishery production caused undeveloped fish processing business and marketing of fisheries products in District Cepiring and the low level of income of small fishing and fish farmers. Thus, the development should be concentrated on two sectors that is the tourism sector, fisheries and marine sector.Keywords: Potential, Problems, Coastal Zone and Coastal Development